Pengaruh aditif fermentasi terhadap kualitas organoleptik dan palatabilitas silase berbasis plastic bag pada sapi perah - Aldena Bina Salimah; Sari Suryanah (Fakultas Pertanian Universitas Majalengka, 2026)
This study evaluated the effects of fermentation additives on the organoleptic quality and palatability of plastic bag-based silage for dairy cattle. Four treatments were applied: control silage, silage supplemented with molasses, silage supplemented with molasses and probiotics, and complete-feed silage supplemented with molasses, probiotics, and concentrate. The results showed that silage treated with molasses and probiotics exhibited the highest aroma score and tended to improve colour and texture, indicating a more favourable fermentation process and better preservation of silage quality. Odour scores were relatively similar among treatments, suggesting that all silages remained within an acceptable quality range. Feeding duration ranged from 246.17 to 301.33 s, while consumption percentage ranged from 56.67% to 62.83%. Although palatability parameters showed no marked differences among treatments, all silages were readily accepted by the animals. Overall, the combination of molasses and probiotics exhibited better sensory quality and favourable palatability, suggesting its potential as the most effective treatment for improving the quality of silage stored in plastic bags.